ON DELTA g*- LOCALLY CLOSED SETS AND LOCALLY CONTINUOUS FUNCTIONS IN TOPOLOGICAL SPACES - Rajesh, sudha - (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
Abstract: In this paper three new classes of locally closed sets are introduced by using dg*-closed sets in topological spaces. Also their continuous functions and irresolute functions are introduced and discussed their properties.